Determination of a sampling method for the "hormiga loca in sugar cane - GOMEZ-L., LUIS ANTONIO; LÓPEZ - DE PULIDO, CONSUELO (Revista Colombiana de Entomología, 1995)
The hormiga loca (crazy ant), Paratrechina fulva (Mayr) (Hymenoptera: Formicidae), was detected in sugarcane fields in the Cauca Valley, and it was necessary to establish a sampling procedure for the management of this pest. A plastic box was tested using different types and amounts of baits, the number of holes, exposure periods, and times during the day. This method was finally compared with another procedure in which the number of ants crossing a square of 10 cm of the side was considered. Using this procedure, boxes were rapidly distributed and picked up in the field and samples could be stored until they can be counted. The most efficient bait was sausage (1/4 slice/trap): eight holes/trap was an adequate number; the sampling time suggested is 30 minutes, at any time in the day. The coefficient of variation of this sampling method was 20% in comparison with 70% of the 10 cm square method. It was suggested to use 50 traps/field to obtain information with a confidence of 80% and ± 10 ants of error.